Importance of a sterile surgical environment during oral surgery (Research, Society and Development, 2023)
Reducing and preventing the risk of infections with disease-causing pathogens is of the utmost importance in dental care, which can be achieved through disinfection and sterilization processes and the use of protective elements. The objective of this study is to publicize the importance of the correct management of a sterile environment during a dental surgical intervention. A search was carried out in the digital databases PubMed, Scielo, Google School, Scine Direct, Dialnet, Academia.edu, where 26 studies were selected, including original articles and theses published between the years 2018-2023, in Spanish and English. Within the dental office, a large number of infectious microorganisms from the oral cavity of patients can be found, the same ones that can be lodged in the instruments and on the work surfaces due to splashes of saliva, blood or other fluids, as well as They can also be found in the air, a product of the generation of aerosols. Proper management of disinfection and sterilization protocols is the fundamental piece to guarantee the health of the patient and clinical staff at the time of performing a surgical intervention.